The Role of Women in Islam in Propagation and Propagation (Special Study of the Prophetic Era): دعوت وتبلیغ میں خواتین اسلام کا کردار (عہدرسالت کا خصوصی مطالعہ) - Panhwar Al-Azhari, Dr. Hafiz Ghulam Anwar; Akram, Dr. Nighat; Malik, Majid Nawaz (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
History has witnessed that women have always actively participated in the propagation of Islam along with men and have not missed a single moment in spreading the religion of Islam. The pages of history are full of great achievements of eminent women in promoting da’wah and propagation. Among them, the mothers of the believers and companions such as Hazrat Khadija al-Kubra (may Allah be pleased with her), Hazrat Aisha Siddiqah (may Allah be pleased with her), Hazrat Fatima al-Zahra (may Allah be pleased with her), Hazrat Sumayyah (may Allah be pleased with her), Hazrat Umm-Umarah (may Allah be pleased with her), Hazrat Safiyyah (may Allah be pleased with her), Hazrat Umm-Salmah (may Allah be pleased with her), Hazrat Asma (may Allah be pleased with her), Hazrat Fatima bint al-Khattab (may Allah be pleased with her) are among the foremost. These women were so passionate about da’wah and propagation that many of the great companions of the Prophet (peace and blessings of Allah be upon them) were influenced by their da’wah and embraced Islam. In carrying out this duty, women were subjected to oppression and persecution. They had to cut off ties with their relatives and even had to say goodbye to their families to protect their faith. However, they patiently and steadfastly faced all kinds of hardships and sufferings that came in the way of truth and did not hesitate to sacrifice their lives for the advancement of Islam.